Nitrate Assimilation in Fusarium fujikuroi Is Controlled by Multiple Levels of Regulation - Pfannmüller, Andreas; Boysen, Jana M.; Tudzynski, Bettina (Frontiers in Microbiology, 2017)
Secondary metabolite production of the phytopathogenic ascomycete fungus Fusarium fujikuroi is greatly influenced by the availability of nitrogen. While favored nitrogen sources such as glutamine and ammonium are used preferentially, the uptake and utilization of nitrate is subject to a regulatory mechanism called nitrogen metabolite repression (NMR). In Aspergillus nidulans, the transcriptional control of the nitrate assimilatory system is carried out by the synergistic action of the nitrate-specific transcription factor NirA and the major nitrogen-responsive regulator AreA. In this study, we identified the main components of the nitrate assimilation system in F. fujikuroi and studied the role of each of them regarding the regulation of the remaining components. We analyzed mutants with deletions of the nitrate-specific activator NirA, the nitrate reductase (NR), the nitrite reductase (NiR) and the nitrate transporter NrtA. We show that NirA controls the transcription of the nitrate assimilatory genes NIAD, NIIA and NRTA in the presence of nitrate, and that the global nitrogen regulator AreA is obligatory for expression of most, but not all NirA target genes (NIAD). By transforming a NirA-GFP fusion construct into the ΔNIAD, ΔNRTA and ΔAREA mutant backgrounds we revealed that NirA was dispersed in the cytosol when grown in the presence of glutamine, but rapidly sorted to the nucleus when nitrate was added. Interestingly, the rapid and nitrate-induced nuclear translocation of NirA was observed also in the ΔAREA and ΔNRTA mutants, but not in ΔNIAD, suggesting that the fungus is able to directly sense nitrate in an AreA- and NrtA-independent, but NR-dependent manner.